Embedded thin film integrated energy storage structure, preparation method and application

CN116387644BActive Publication Date: 2026-10-27SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310409133.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2026-10-27
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

现有的储能体系主要集中在锂离子电池,相比较水系锌离子电池,锂离子电池存在成本高、组装且运行环境苛刻、安全性差等问题,且嵌入的电池通常比较厚,对碳纤维增强复合材料层合板的力学影响比较大(Composites Part A:Applied Science and Manufacturing,2020,136:105966.Composites Science and Technology,2008,68(7-8):1935-1941.)

Benefits of technology

[0015]本发明所提供的嵌入型薄膜一体化储能结构能够取代传统的电池组,将储能器件直接集成到系统本身所需的结构支撑上,使得整体设备系统的结构更加紧凑和简单,有效实现空间、质量和成本上的节省;另外,相比较繁琐的传统碳纤维增强环氧真空固化工艺组装的嵌入型结构储能器件,本发明提供的嵌入型薄膜一体化储能结构在实现结构精准性、模型多样性和材料可回收性方面有着更为显著的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116387644B_ABST
    Figure CN116387644B_ABST
Patent Text Reader

Abstract

The application discloses an embedded thin film integrated energy storage structure, a preparation method and application. The preparation method comprises the following steps: forming a structure precursor, which has an open accommodating space; placing a thin film energy storage device into the accommodating space; continuing to cover the printing material by 3D printing, so that the opening is closed or reduced, and a 3D printing structure is formed; pouring fixing glue into the accommodating space, and obtaining the embedded thin film integrated energy storage structure. The embedded thin film integrated energy storage structure provided by the application can replace a traditional battery pack, and directly integrates the energy storage device to a required structure support of the system itself, so that the space, mass and cost are effectively saved. In addition, compared with the embedded structure energy storage device assembled by a complicated traditional carbon fiber reinforced epoxy vacuum curing process, the embedded thin film integrated energy storage structure provided by the application has more remarkable advantages in realizing structure precision, model diversity and material recyclability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of structural energy storage materials technology, and in particular to an embedded thin-film integrated energy storage structure, its preparation method and application. Background Technology

[0002] Reducing greenhouse gas emissions, improving fuel economy, and optimizing energy storage systems are key requirements for electric and hybrid vehicles. Reducing vehicle weight and using load-bearing energy storage systems are methods to meet these requirements. Current methods for reducing vehicle weight involve replacing heavy body and chassis materials, such as steel, with lighter carbon fiber reinforced polymer (CFRP) laminates and sandwich composites. However, a drawback of using electricity as a drive system in current designs is the need for a large number of high-energy-storage batteries, which requires significant vehicle space and greatly increases vehicle weight. To achieve this, researchers have proposed the concept of multifunctional composite materials, where a single material or structure performs two or more functions. In recent years, multifunctional carbon fiber reinforced composites (combining high mechanical strength with good energy storage capacity) have attracted considerable attention in the field of structural energy storage devices (Journal of Composite Materials, 2009, 43(5): 549-560). Currently, one method for achieving integrated structural energy storage is to directly embed energy storage devices into carbon fiber reinforced composites. This type of embedded structural energy storage is highly favored due to its simple manufacturing process and ability to easily balance structural support and energy storage functions, and it has great application prospects in the design of future structural energy storage systems.

[0003] To date, embedded batteries are mainly divided into two categories: pouch lithium-ion batteries and thin-film lithium-ion batteries. Existing energy storage systems mainly focus on lithium-ion batteries. Compared with aqueous zinc-ion batteries, lithium-ion batteries have problems such as high cost, harsh assembly and operating environment, and poor safety. Moreover, the embedded batteries are usually relatively thick, which has a greater impact on the mechanical properties of carbon fiber reinforced composite laminates (Composites Part A: Applied Science and Manufacturing, 2020, 136: 105966. Composites Science and Technology, 2008, 68(7-8): 1935-1941.). In addition, embedded structure energy storage is still in the early stage of experimentation. The experimental results are relatively scattered and lack relevant theoretical analysis models and evaluation mechanisms. The comprehensive performance of structure energy storage needs to be improved [1]. Existing carbon fiber reinforced structure energy storage research mainly uses the traditional carbon fiber reinforced epoxy vacuum curing process to assemble embedded structure energy storage devices (Composite Structures, 2019, 220(15): 677-686. Energy Storage Materials, 2020, 24: 676-681.). This embedded structure energy storage process is complicated. Although it can save the volume of the system, it is difficult to achieve lightweight, structural diversification and recycling of carbon fiber reinforced composite materials. Therefore, in the future development of structure energy storage, it is urgent for us to develop new structure energy storage systems to achieve the controllable assembly of efficient and lightweight structure energy storage devices.

[0004] By combining traditional carbon fiber reinforced epoxy curing process with novel thermoplastic carbon fiber 3D printing technology, we embed zinc-manganese thin-film batteries into carbon fiber sandwich structures to assemble embedded carbon fiber reinforced zinc-manganese structure batteries, which can achieve more significant advantages in terms of structural precision, model diversity and material recyclability. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an embedded thin-film integrated energy storage structure, its preparation method, and its application.

[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0007] In a first aspect, the present invention provides a method for preparing an embedded thin-film integrated energy storage structure, comprising:

[0008] A structural precursor is formed by 3D printing, wherein the structural precursor has an open accommodating space.

[0009] The thin-film energy storage device is placed into the accommodating space;

[0010] Continue to cover the structural precursor with printing material by 3D printing to close or reduce the opening, forming a 3D printed structure;

[0011] A fixing adhesive is injected into the closed or reduced accommodating space to integrate the thin-film energy storage device with the 3D printed structure, thereby obtaining an embedded thin-film integrated energy storage structure.

[0012] Secondly, the present invention also provides an embedded thin-film integrated energy storage structure prepared by the above-mentioned preparation method.

[0013] Thirdly, the present invention also provides an application of the above-mentioned embedded thin-film integrated energy storage structure in the manufacture of vehicles.

[0014] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention include at least the following:

[0015] The embedded thin-film integrated energy storage structure provided by this invention can replace traditional battery packs, directly integrating energy storage devices into the structural support required by the system itself, making the overall equipment system more compact and simple, and effectively saving space, weight and cost. In addition, compared with the cumbersome traditional embedded structure energy storage devices assembled by carbon fiber reinforced epoxy vacuum curing process, the embedded thin-film integrated energy storage structure provided by this invention has more significant advantages in achieving structural accuracy, model diversity and material recyclability.

[0016] The above description is merely an overview of the technical solution of the present invention. In order to enable those skilled in the art to better understand the technical means of this application and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described below in conjunction with detailed drawings. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of a quasi-solid-state flexible zinc-manganese thin-film battery structure provided in a typical embodiment of the present invention;

[0018] Figure 2 This is a flowchart of a 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin-film battery fabrication process according to a typical embodiment of the present invention.

[0019] Figure 3 This is an optical photograph of a 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery with different battery embedding numbers provided in a typical embodiment of the present invention;

[0020] Figure 4 This is a comparative test diagram of the tensile properties of a 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery with different battery embedding numbers provided in a typical embodiment of the present invention.

[0021] Figure 5 This is a typical embodiment of the present invention, showing the GCD curve test diagram of a 3D printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery under different tensile loads.

[0022] Figure 6 This is a comparative test chart of the specific capacity of a 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery under different tensile loads, provided by a typical embodiment of the present invention.

[0023] Figure 7 This is a comparative test diagram of the bending performance of a 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery provided in a typical embodiment of the present invention;

[0024] Figure 8a This is an example diagram (open circuit state) of a 3D printed carbon fiber reinforced structure energy storage model provided in another typical embodiment of the present invention;

[0025] Figure 8b This is an example diagram (connected state) of a 3D printed carbon fiber reinforced structure energy storage model provided in another typical embodiment of the present invention. Detailed Implementation

[0026] In view of the shortcomings of the prior art, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention. The following will further explain and illustrate this technical solution, its implementation process, and its principles.

[0027] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0028] See Figure 2 As shown, this embodiment of the invention provides a method for fabricating an embedded thin-film integrated energy storage structure, which includes the following steps:

[0029] A structural precursor is formed by 3D printing, wherein the structural precursor has an open accommodating space.

[0030] The thin-film energy storage device is placed into the accommodating space.

[0031] Continue 3D printing by covering the precursor structure with printing material to close or reduce the opening, thus forming a 3D printed structure. A 3D printed structure refers to an outer layer structure that wraps around and restricts the position of the energy storage device. The opening can be completely closed or reduced to a degree that prevents the energy storage device from detaching.

[0032] A fixing adhesive is injected into the closed or reduced accommodating space to integrate the thin-film energy storage device with the 3D printed structure, thereby obtaining an embedded thin-film integrated energy storage structure.

[0033] In some embodiments, the thin-film energy storage device is selected from zinc-manganese thin-film batteries, and a typical zinc-manganese thin-film battery structure is as follows: Figure 1 As shown; meanwhile, zinc-manganese thin-film batteries have the advantages of safe and pollution-free operation environment, and their extremely thin thickness and excellent tensile and tensile strength also make the battery have a small mechanical impact on the fiber-reinforced composite laminate.

[0034] In some embodiments, the zinc-manganese thin-film battery includes a MnO2 composite film electrode, an electrolyte, and a zinc electrode sequentially bonded together. The zinc electrode, serving as the negative electrode, may include, for example, a zinc sheet or a zinc powder / graphene / CNT composite electrode.

[0035] In some embodiments, the electrolyte is selected from quasi-solid electrolytes, more preferably gel electrolytes, which may include, for example, PVA, CMC, etc., but are not limited thereto.

[0036] In some embodiments, the MnO2 composite film electrode is selected from MnO2 / CNT composite films, or other MnO2 composite film electrodes. The MnO2 / CNT composite film is formed by loading MnO2 nanosheets onto carbon microsheets and blending them with carbon nanotubes.

[0037] In some embodiments, the MnO2 / CNT composite film is formed by coating a slurry containing carbon microsheets and carbon nanotubes supported on MnO2 nanosheets.

[0038] As a typical application example of the above technical solution, the fabrication process of the zinc-manganese thin-film battery can, for example, adopt the following steps:

[0039] (1) The porous carbon microsheets (CT)@MnO2 composite material can be prepared by referring to the existing technical solutions that have been disclosed, preferably by in-situ ultrasonic method.

[0040] (2) Using CT@MnO2 composite material as active material and carbon nanotubes as conductive network and structural support, MnO2 composite thin film electrode was prepared by traditional coating process.

[0041] (3) The prepared CT@MnO2 composite flexible thin film electrode is used as the positive electrode and the zinc sheet is used as the negative electrode to assemble a quasi-solid-state flexible zinc-manganese thin film battery.

[0042] Specifically, for example, activated carbon microsheets and potassium permanganate are used as raw materials, and CT@MnO2 composite materials are prepared through secondary carbonization and ultrasonic synthesis processes. Using CT@MnO2 composite materials as the active material and carbon nanotubes as the conductive network and structural support, MnO2 composite thin-film electrodes are prepared using traditional coating processes. The prepared CT@MnO2 composite flexible thin-film electrode is used as the positive electrode, and zinc sheets are used as the negative electrode to assemble a quasi-solid-state flexible zinc-manganese thin-film battery. The positive electrode formed by the composite of carbon microsheets, manganese dioxide nanosheets, and carbon nanotubes, as well as the flexible separator, gel electrolyte, and zinc-platinum or other zinc composite electrodes, all possess excellent flexibility and tensile properties. This allows for good mechanical matching with 3D printed structures, especially carbon fiber reinforced nylon printed structures, resulting in integrated batteries with excellent tensile and bending resistance, particularly in maintaining a considerable level of battery capacity during stretching and bending.

[0043] Based on the preparation of the above-mentioned thin-film battery, the embodiments of the present invention also employ 3D printing equipment, preferably using carbon fiber / nylon composite fiber fused filaments as filaments, designing a thin-film battery embedding model through modeling, and finally assembling an embedded 3D printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin-film structure battery through epoxy resin infusion.

[0044] In some implementations, the outer layer of the thin-film energy storage device is coated with encapsulating adhesive.

[0045] In some embodiments, the encapsulating adhesive is selected from polyimide.

[0046] In some implementations, the positive and negative electrodes of the thin-film energy storage device are also electrically connected to tabs, which extend from the accommodating space to the outer surface of the 3D printed structure.

[0047] In some embodiments, the 3D printed filaments include fiber-reinforced filaments, which are formed from at least a composite of a thermoplastic polymer and reinforcing fibers.

[0048] In some embodiments, the thermoplastic polymer includes any one or a combination of two or more of nylon, polyphenylene sulfide, polyvinyl alcohol, polylactic acid, and polyetherketoneketone, with nylon being more preferred.

[0049] In some embodiments, the reinforcing fiber includes any one or a combination of two or more of carbon fiber, glass fiber, graphite fiber, and aramid fiber, preferably carbon fiber.

[0050] In some embodiments, the reinforcing fibers are continuous filaments and / or chopped strands.

[0051] In some embodiments, the printing filament further includes reinforcing fillers distributed in the thermoplastic polymer, including any one or a combination of two or more of carbon black, carbon nanotubes, and graphene.

[0052] In some embodiments, the fixing adhesive is selected from thermosetting resin adhesives.

[0053] In some embodiments, the preparation method specifically includes:

[0054] The thermosetting resin adhesive is poured into the accommodating space and then cured.

[0055] In some embodiments, the thermosetting resin adhesive includes any one or a combination of two or more of epoxy resin, phenolic resin, polyester resin, vinyl ester, bismaleimide, thermosetting polyimide, and cyanate ester.

[0056] As a specific application example of the above technical solution, carbon fiber reinforced nylon composite fiber filament is used as the 3D printing filament. Using 3D printing equipment, a thin-film battery embedding model is designed through modeling. Finally, through a small amount of epoxy infusion, the assembly of an embedded 3D printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin-film battery structure is achieved.

[0057] The specific process is as follows:

[0058] Design 3D printed models.

[0059] During the printing process, zinc-manganese thin-film batteries are embedded into the groove-shaped structure of the 3D printed model.

[0060] Continue with carbon fiber 3D printing for encapsulation.

[0061] Epoxy resin was injected as a binder to fill the gap between the quasi-solid-state thin-film flexible zinc-manganese battery and the 3D-printed shell, and the battery was bonded to the carbon fiber structural reinforcement. After curing at room temperature, the final embedded 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin-film structure battery was obtained.

[0062] By adjusting different 3D printing models, it is possible to achieve integrated design of batteries with different zinc-manganese structures.

[0063] The 3D printing filament includes any one or a combination of two or more of nylon, polyphenylene sulfide, polyvinyl alcohol, polylactic acid, and polyetherketoneketone, and is not limited thereto.

[0064] Furthermore, the thermoplastic polymer includes, but is not limited to, nylon; when the thermoplastic polymer is polyvinyl alcohol, the 3D printing temperature is 230–250°C; when the thermoplastic polymer is polyphenylene sulfide, the 3D printing temperature is 285–330°C; when the thermoplastic polymer is polylactic acid, the 3D printing temperature is 170–230°C; and when the thermoplastic polymer is polyetherketoneketone, the 3D printing temperature is 305–380°C. In summary, the 3D printing process is performed under set temperature conditions, wherein the set temperature is greater than or equal to the melting point of the thermoplastic polymer and lower than its decomposition temperature.

[0065] Furthermore, the reinforcing fibers may include, for example, one or more combinations of carbon fibers, glass fibers, graphite fibers, aramid fibers, etc., and are not limited thereto. It may also include, as reinforcing fillers, one or more combinations of powder fillers such as carbon black, carbon nanotubes, graphene, etc., that can be uniformly dispersed in the resin, and is not limited thereto.

[0066] In some more specific implementations, the thin-film battery used can be adjusted as needed. The 3D printed model can be adjusted according to the size of the thin-film battery used. The number of thin-film batteries that can be placed in the 3D printed model can be one, two, three, or a combination thereof, and is not limited to this. Multiple thin-film batteries in the 3D printed model can be arbitrarily connected in series, parallel, or placed independently.

[0067] In some specific embodiments, epoxy resin is infused as a binder to fill the gap between the quasi-solid-state thin-film flexible zinc-manganese battery and the 3D-printed housing. The binder may include, for example, epoxy resin, phenolic resin, polyester resin, vinyl ester, bismaleimide, thermosetting polyimide, cyanate ester, etc., and is not limited to these. After adding a curing agent, the binder is cured at a curing temperature to obtain the final embedded 3D-printed carbon fiber reinforced zinc-manganese structure battery. Specifically, for example, when the binder is phenolic resin, curing is performed at room temperature for 24 hours, and the curing time decreases as the curing temperature increases; when the binder is polyester resin, curing is performed at room temperature for 24 hours, and the curing time decreases as the curing temperature increases.

[0068] A second aspect of this invention also provides an embedded thin-film integrated energy storage structure prepared by the above-described method, wherein the prepared sample of the energy storage structure is as follows: Figure 3 As shown, one or more energy storage devices can be embedded in it.

[0069] A second aspect of the present invention also provides the application of the above-described embedded thin-film integrated energy storage structure in vehicle manufacturing, for example, in the manufacture of a lightweight automobile frame, the above-described technical solution is used to form a vehicle body structure with an integrated battery frame.

[0070] The technical solution of the present invention will be further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only for illustrating the present invention and do not limit the scope of the present invention.

[0071] Example 1

[0072] This embodiment illustrates the preparation process of a zinc-manganese thin-film battery, as detailed below:

[0073] (1) Cut the CT@Mn02 / CNT composite thin film electrode, zinc sheet and diaphragm into pieces with a size of 1cm×3cm.

[0074] (2) Add 13.6g ZnCl2 and 3.0g MnSO4·H2O to 50mL of deionized water, then heat to 85℃ and stir. After the solution becomes clear, slowly add 5g PVA particles and continue stirring for 2h. After homogenization, PVA / ZnCl2-MnSO4 gel electrolyte is obtained.

[0075] (3) Adhere conductive copper glue to the positive and negative zinc foils (thickness 0.05mm) and bring out the battery tabs.

[0076] (4) Before assembly, the separator and positive electrode material are vacuum pre-impregnated in the electrolyte. Keep for 30 minutes to ensure that the electrolyte can fully wet the separator and fully combine with the positive electrode active material. Then let stand at room temperature for 1 hour to remove some of the moisture.

[0077] (5) The positive electrode, separator, and negative electrode (zinc foil; thickness 0.05 mm) coated with gel electrolyte are stacked and assembled in sequence to obtain a flexible zinc-manganese thin film battery, and then dried at 40°C for 1 hour to further remove some moisture.

[0078] (6) Finally, high-temperature resistant polyimide (PI) is used for encapsulation to obtain the final quasi-solid-state flexible zinc-manganese thin-film battery, the structure of which is as follows: Figure 1 As shown.

[0079] Example 2

[0080] This embodiment illustrates the fabrication process of an integrated energy storage structure, as detailed below:

[0081] (1) Design a 3D printed mechanical component model based on the size of the zinc-manganese thin film battery (30mm×10mm×0.7mm).

[0082] (2) During the printing process, a zinc-manganese thin film battery is embedded into the groove structure in the 3D printed model. The groove size is 32mm×12mm×1mm.

[0083] (3) Continue to encapsulate carbon fiber reinforced nylon 3D printing at 260℃.

[0084] (4) Infuse epoxy resin to fill the gap between the quasi-solid-state thin-film flexible zinc-manganese battery and the 3D-printed shell, then bond the battery to the carbon fiber structural reinforcement. After curing at room temperature for 24 hours, the final embedded 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin-film structure battery is obtained. Figure 3 As shown in the first column, an integrated printed structure with a single battery is obtained.

[0085] Example 3

[0086] This embodiment also illustrates the fabrication process of the integrated energy storage structure, as detailed below:

[0087] (1) Design a 3D printed mechanical component model based on the size of the zinc-manganese thin film battery (30mm×10mm×0.7mm).

[0088] (2) During the printing process, two or three zinc-manganese thin film batteries are respectively embedded into the groove structure in the two 3D printed models. The groove size is 32mm×12mm×1mm.

[0089] (3) Carbon fiber reinforced nylon 3D printing encapsulation was carried out at 260℃.

[0090] (4) Infuse epoxy resin to fill the gap between the quasi-solid-state thin-film flexible zinc-manganese battery and the 3D-printed shell, then bond the battery to the carbon fiber structural reinforcement. After curing at room temperature for 24 hours, the final embedded 3D-printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin-film structure battery is obtained. Figure 3 The second and third columns are shown in the diagram.

[0091] Tests showed that the tensile properties of the 3D-printed mechanical parts with different numbers of embedded batteries obtained in Examples 2 and 3 were as follows: Figure 4 As shown, the bending properties are as follows Figure 5 As shown.

[0092] Furthermore, this invention also tested the capacity retention performance of the printed integrated energy storage structure under load, and the results are as follows: Figure 6 As shown in the figure, the integrated energy storage structure prepared by this invention exhibits excellent specific capacity retention before complete failure. The bending resistance test results are as follows... Figure 7 As shown, it can be seen that the integrated energy storage structure prepared by the present invention can still output electrical energy even under extreme bending.

[0093] Example 4

[0094] This embodiment also illustrates the fabrication process of the integrated energy storage structure, as detailed below:

[0095] (1) Design a 3D printed mechanical component model based on the size of the zinc-manganese thin film battery (30mm×10mm×0.7mm).

[0096] (2) During the printing process, one zinc-manganese thin film battery is embedded into the groove structure of the two 3D printed models respectively. The groove size is 32mm×12mm×1mm.

[0097] (3) Carbon fiber reinforced nylon 3D printing encapsulation was carried out at 260℃.

[0098] (4) Inject epoxy resin to fill the gap between the quasi-solid-state thin film flexible zinc-manganese battery and the 3D printed shell, bond the battery to the carbon fiber structure reinforcement, and cure at 80°C for 12 hours to obtain the final embedded 3D printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery.

[0099] Example 5

[0100] This embodiment also illustrates the fabrication process of the integrated energy storage structure, as detailed below:

[0101] (1) Design a 3D printed mechanical component model based on the size of the zinc-manganese thin film battery (30mm×10mm×0.7mm).

[0102] (2) During the printing process, one zinc-manganese thin film battery was embedded into the groove structure of the two 3D printed models respectively. The groove size was 321mm×12mm×1mm.

[0103] (3) Carbon fiber reinforced polyphenylene sulfide 3D printing encapsulation was carried out at 320℃.

[0104] (4) Inject epoxy resin to fill the gap between the quasi-solid-state thin film flexible zinc-manganese battery and the 3D printed shell, bond the battery to the carbon fiber structure reinforcement, and cure at 80°C for 12 hours to obtain the final embedded 3D printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery.

[0105] Example 6

[0106] This embodiment also illustrates the fabrication process of the integrated energy storage structure, as detailed below:

[0107] (1) Design a 3D printed mechanical component model based on the size of the zinc-manganese thin film battery (30mm×10mm×0.7mm).

[0108] (2) During the printing process, one zinc-manganese thin film battery is embedded into the groove structure of the two 3D printed models respectively. The groove size is 32mm×12mm×1mm.

[0109] (3) Carbon fiber reinforced nylon 3D printing encapsulation was carried out at 260℃.

[0110] (4) Phenolic resin is injected as a binder to fill the gap between the quasi-solid-state thin film flexible zinc-manganese battery and the 3D printed shell, and the battery is bonded to the carbon fiber structure reinforcement. After curing at room temperature for 24 hours, the final embedded 3D printed carbon fiber reinforced quasi-solid-state flexible zinc-manganese thin film structure battery is obtained.

[0111] Example 7

[0112] This embodiment also illustrates the fabrication process of an integrated energy storage structure. Using 3D printing technology, different model structure battery components can be assembled, and it can be printed to form the shape of a flowerpot. Its on / off state is as follows: Figure 8a and Figure 8b As shown.

[0113] Comparative Example 1

[0114] The method is similar to Example 1, except that a commercially available solid-state lithium-ion flexible thin-film battery is embedded into the 3D-printed mechanical component model. Due to the harsh encapsulation environment (oxygen-free and water-free), low ionic conductivity of the solid electrolyte, and poor safety, the electrical performance of the resulting mechanical component model is inferior to that of the 3D-printed mechanical component model assembled with a quasi-solid-state thin-film flexible zinc-manganese battery. This is particularly evident when the bending degree reaches... Figure 2 When the LED strip reaches the second column from the left, its battery discharge capacity drops drastically, making it unable to light up.

[0115] Comparative Example 2

[0116] This embodiment illustrates the fabrication process of an integrated zinc-manganese thin-film battery using a traditional carbon fiber vacuum epoxy process. The details are as follows:

[0117] (1) Cut 4 pieces of carbon fiber fabric (CF) with a size of 160mm×30mm;

[0118] (2) Prepare epoxy resin (Resin) by mixing epoxy resin and curing agent at a mass ratio of 5:1;

[0119] (3) The epoxy resin fully impregnates the carbon fiber fabric;

[0120] (4) The carbon fiber fabric pre-impregnated with epoxy resin is laid and folded layer by layer, and the assembled quasi-solid flexible zinc-manganese thin film battery (30mm×10mm×0.5mm) is sandwiched in the middle of the carbon fiber layer to form a typical sandwich structure.

[0121] (5) The assembled sandwich structure is placed in a mold and sealed in a vacuum bag. After curing at 30°C for 24 hours, it is demolded and cut to obtain the final conventional embedded carbon fiber reinforced zinc-manganese structure battery (size 150mm×25mm×2mm).

[0122] The assembled embedded carbon fiber reinforced zinc-manganese structure battery has a tensile strength and tensile modulus of up to 266.5 MPa and 25.3 GPa, respectively, and a bending strength and bending modulus of up to 218 MPa and 26 GPa, respectively. However, when the battery is at 80% of the ultimate tensile or bending failure stress, the assembled zinc-manganese structure battery exhibits extremely poor energy storage performance, which can lead to a sharp drop or even loss of discharge capacity. Furthermore, the manufacturing process of this embodiment is relatively complex and not conducive to industrial applications.

[0123] This is because, although vacuum epoxy process is a mature carbon fiber model making process, the carbon fiber structure and the battery inside are not matched in terms of modulus and hardness. As a result, the battery inside will be damaged when the model is deformed, which in turn leads to a decrease in battery performance during deformation.

[0124] Based on the above test results, it is clear that the embedded thin-film integrated energy storage structure provided by the embodiments of the present invention can replace the traditional battery pack, directly integrating the energy storage device into the structural support required by the system itself, making the overall equipment system structure more compact and simple, and effectively achieving savings in space, weight and cost. In addition, compared with the cumbersome traditional embedded structure energy storage device assembled by the carbon fiber reinforced epoxy vacuum curing process, the embedded thin-film integrated energy storage structure provided by the present invention has more significant advantages in achieving structural accuracy, model diversity and material recyclability.

[0125] It should be understood that the above embodiments are merely illustrative of the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for fabricating an embedded thin-film integrated energy storage structure, characterized in that, include: A structural precursor is formed by 3D printing, wherein the structural precursor has an open accommodating space, and the printing filament of the 3D printing includes fiber-reinforced filament, which is formed by at least a composite of thermoplastic polymer and reinforcing fiber. The thermoplastic polymer includes any one or a combination of two or more of nylon, polyphenylene sulfide, polyvinyl alcohol, polylactic acid, and polyetherketoneketone, and the reinforcing fiber includes any one or a combination of two or more of carbon fiber, glass fiber, graphite fiber, and aramid fiber. A thin-film energy storage device is placed in the accommodating space. The thin-film energy storage device is selected from a zinc-manganese thin-film battery. The zinc-manganese thin-film battery includes a MnO2 composite membrane electrode, an electrolyte, and a zinc electrode that are sequentially bonded together. The electrolyte is selected from a gel electrolyte. The MnO2 composite membrane electrode is selected from a MnO2 / CNT composite film. The MnO2 / CNT composite film is formed by loading MnO2 nanosheets onto carbon microsheets and blending them with carbon nanotubes. The MnO2 / CNT composite film is formed by coating a coating slurry containing MnO2 nanosheets loaded with carbon microsheets and carbon nanotubes. Continue to cover the structural precursor with printing material by 3D printing to close or reduce the opening, forming a 3D printed structure; A thermosetting resin binder is injected into the accommodating space and cured. The thermosetting resin binder includes any one or a combination of two or more of epoxy resin, phenolic resin, polyester resin, vinyl ester, bismaleimide, thermosetting polyimide, and cyanate ester, so that the thin-film energy storage device is integrated with the 3D printed structure to obtain an embedded thin-film integrated energy storage structure.

2. The preparation method according to claim 1, characterized in that, The outer layer of the thin-film energy storage device is wrapped with an encapsulating adhesive selected from polyimide. The positive and negative electrodes of the thin-film energy storage device are also electrically connected to tabs, which extend from the accommodating space to the outer surface of the 3D printed structure.

3. The preparation method according to claim 1, characterized in that, The thermoplastic polymer is selected from nylon, and the reinforcing fiber is selected from carbon fiber.

4. The preparation method according to claim 1, characterized in that, The reinforcing fiber is a continuous filament and / or a chopped filament. The printing wire also includes reinforcing fillers distributed in the thermoplastic polymer. The reinforcing fillers include any one or a combination of two or more of carbon black, carbon nanotubes, and graphene.

5. An embedded thin-film integrated energy storage structure prepared by the preparation method according to any one of claims 1-4.

6. The application of the embedded thin-film integrated energy storage structure as described in claim 5 in the manufacture of vehicles.

Citation Information

Patent Citations

  • Carbon / manganese dioxide composite material and preparation method and application thereof

    CN114899385A

  • Multifunctional energy storage composites

    US20180040912A1

  • Preparation method for thin-film capacitor, and thin-film capacitor

    WO2022040987A1